1981
DOI: 10.1093/ajcn/34.3.328
|View full text |Cite
|
Sign up to set email alerts
|

Effect of test meals of varying dietary fiber content on plasma insulin and glucose response

Abstract: To assess the effect of dietary fiber on glucose tolerance four different meals of varying fiber content but identical protein fat and carbohydrate content were fed to eight healthy men aged 22 to 45. Each meal provided 75 g of carbohydrate as liquid glucose formula, as brown rice, pinto beans, or All Bran. The mean plasma glucose and insulin responses were highest following the formula, and least for All Bran and pinto beans. Rice produced nearly as great a rise in insulin and glucose as did the formula. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

1982
1982
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(46 citation statements)
references
References 23 publications
1
44
0
1
Order By: Relevance
“…Potter et al [20] assessed the effect of dietary fiber on the glucose response to 3 different diets of varying fiber content (18, 16.2 and 2.8 g) but identical protein, fat and carbohydrate content fed to 8 healthy men aged 22 to 45 years. They found that the lowest glucose response occurred in the group with a dietary fiber intake of 18 g per day and the highest occurred in the group with 2.8 g of dietary fiber per day.…”
Section: Discussionmentioning
confidence: 99%
“…Potter et al [20] assessed the effect of dietary fiber on the glucose response to 3 different diets of varying fiber content (18, 16.2 and 2.8 g) but identical protein, fat and carbohydrate content fed to 8 healthy men aged 22 to 45 years. They found that the lowest glucose response occurred in the group with a dietary fiber intake of 18 g per day and the highest occurred in the group with 2.8 g of dietary fiber per day.…”
Section: Discussionmentioning
confidence: 99%
“…A large number of clinical investigations after the mid-1970 s reported the effects of dietary fibre on metabolic responses in normal and diabetic subjects [39,[40][41][42][43][44][45][46][47]. Among randomized crossover studies of high and low fibre intake in natural food form and administered under isocaloric conditions, the most consistent finding has been an inverse association between fibre intake and postprandial insulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary fiber alters postprandial glycemia and insulinemia in both healthy (9,16) and diabetic subjects (9,17,18). Many of the studies reporting such effects of fiber have tested isolated fiber sources independent of consumption of a complete mixed meal.…”
Section: Introductionmentioning
confidence: 99%